"Just because you're pregnant, doesn't mean you're sick!" A qualitative study of beliefs regarding physical activity in black South African women. Issue 1 (December 2016) - Watson, Estelle; Norris, Shane; Draper, Catherine; Jones, Rachel; van Poppel, Mireille; Micklesfield, Lisa
Abstract Background Despite the benefits of physical activity during pregnancy, the physiological and psychological changes that occur during this unique period may put women at greater risk of being sedentary. Lifestyle and environmental transitions have left black South African women at increased risk of physical inactivity and associated health risks. Therefore, the aim of this qualitative study was to describe the beliefs regarding physical activity during pregnancy in an urban African population. Methods Semi-structured interviews (n  = 13) were conducted with pregnant black African women during their third trimester. Deductive thematic analysis was completed based on the Theory of Planned Behaviour. Coding and analysis was completed with the assistance of ATLAS.ti software. Results Participants had a mean age of 28 (19–41) years, and a mean BMI of 30 (19.6–39.0) kg/m2 . Although the majority of women believed that physical activity was beneficial, this did not appear to translate into behaviour. Reported reasons for this included barriers such as pregnancy-related discomforts, lack of time, money and physical activity related education, all of which can contribute to a reduced perceived control to become active. Opportunities to participate in group exercise classes was a commonly reported facilitator for becoming active. In addition, influential role players, such as family, friends and healthcare providers, as well as cultural beliefs, reportedly provided the women with vague, conflicting and often discouraging advice about physical activity during pregnancy. Conclusions This study provides new theoretical insight on the beliefs of urban South African pregnant women regarding physical activity. Findings from this study suggest a holistic approach to improve physical activity compliance during pregnancy, inclusive of physical activity education and exercise opportunities within a community setting. This study presents critical formative work upon which contextually and culturally sensitive interventions can be developed.